A Kind of Novel Analytical Approximate Solution to the Duffing Oscillator. Issue 5 (February 2019) - Qin, Yupeng; Zou, Li; Wang, Zhen; Yu, Zongbing
Abstract: In this paper, a kind of novel analytical approximate solution was constructed to the Duffing oscillator via a modified homotopy analysis method (HAM), namely the piecewise perturbation method (PPM). The validity and efficient of the obtained PPM solutions were investigated by comparing with the traditional HAM solution. The main advantage of the PPM is that it possesses higher accuracy and faster convergence rate than the traditional HAM.